PERSEPSI KONSUMEN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK TELKOMSEL PADA OUTLET ZIFACELL - Mustika, Rita; Ricky, Ricky; Elina, Tuti; Hambani, Pebri (Universitas Bina Bangsa, 2024)
The development of digital technology can be a business opportunity in today's era, one of which is the sale of cellular telecommunications products in the form of Telkomsel. This study aims to test the influence of consumer perception and brand image on purchasing decisions in purchasing Telkomsel products at the Zifacell Outlet in Lubuk Lintah Padang. This study is a quantitative study. The population of this study were consumers who purchased Telkomsel products at the Zifacell outlet in Lubuk Lintah Padang in January as many as 1,256 people. The sample was determined by non-probability sampling, purposive sampling type, obtained a total of 93 consumers. The data in this study were taken through a questionnaire that had been tested for validity and reliability. Data were analyzed descriptively and inferentially. Before conducting the hypothesis test, normality, multicollinearity, heteroscedasticity, and multiple regression analysis were tested. The hypothesis test in this study used the T Test. The results of the study showed that consumer perception and brand image had a positive and significant effect on purchasing decisions for Telkomsel products at Zifacell in Lubuk Lintah Padang. Thus, the results of this study can be used as input for Zifacell in Lubuk Lintah Padang to always provide good service and maintain brand image so that consumer purchasing decisions can be maintained and increased to buy Telkomsel products at Zifacell in Lubuk Lintah Padang